Effects of Eucalyptus tree plantations on soil seed bank and soil physicochemical properties of Qimbaba forest - Kassa, G.; Molla, E.; Abiyu, A. (Informa UK Limited, 2019)
Qimbaba, a prioritized forest area in the northwest of Ethiopia. However, it is experiencing deforestation that limits restoration possibilities. Hence, a detailed assessment of soil seed bank composition and regeneration potential could permit to improve the management of the forests. The study aimed at comparing native with plantation relative to the soil seed bank, as well as their effect on soil properties. A total of 40 circular sample plots (314 m2) were established, half in the natural and half in the plantation forests. Aboveground vegetation was recorded in each plot. Samples were collected for the soil seed bank analysis in the litter layer and the top 9 cm of the soil (3 cm layers) and for soil analysis down to 30 cm (15 cm depths). Vegetation and soil seed bank composition were compared and the effect of forest type (natural vs plantation) on soil seed bank and soil physical and chemical parameters was evaluated. A total of 14 plant species (11 families) were recovered from the soil seed bank (12 species in the natural and 7 in plantation forest). The soil seed bank was not similar according to the Sorenson’s similarity values. There were 11,022 and 10,667 seeds/m2 in the soil seed bank of the natural and plantation forest, respectively. There was no significant difference between the two forests in bulk density, CEC and P but SOC, N, and K were significantly higher in natural. Plantation forest pH was significantly lower than the natural forest.